Workshop Pembuatan dan Publikasi Artikel Ilmiah di Jurnal atau Prosiding untuk Dosen dan Mahasiswa - Dona Fitriawan; Dede Suratman; Edy Yusmin; Ahmad Yani T.; Dian Ahmad Budhysatrya; Romal Ijuddin (IKIP PGRI Bojonegoro, 2023)
ABSTRACTThis service activity began with the publication conditions of lecturers and students which were felt to be very lacking in both proceedings and journals on a national and international scale in West Kalimantan. This form of service is a workshop or training